Social advertising in the system of management of social opinion while COVID pandemics - Chalaganidze, Ekaterina (The International tax journal, 2024)
In the contemporary world social, economic and political conditions face the public with a new reality. The existing social problems, such as health care problems, ecological and other issues are supplemented with the comprehensive pandemics – COVID 19, which became a new reality all over the world. For the purpose of researching of social advertising messages several methods of research had been applied: a content analysis of scientific literature and internet sources, monitoring of sources, auditory analysis, content analysis, ethnographic research which gave us an opportunity to obtain a universal information on the target audience, that, in its turn, is a basis for refining of the strategy of messages and social advertising campaigns. While researching of the impact of the social advertising in the period of COVID pandemics, for better understanding of its efficiency and key mechanisms several theories had been applied: Health Believes Model – 1950, I. Rozenstok, G. Hochbaum, S. Kogels, H. Leventals), Theory of Planned Behavior (TPB- Icek Ajzen, 1985) and Crisis and Emergent Risks Communication Model (CERC).